2007
DOI: 10.2337/db06-0823
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide- and Oxidant-Induced Insulin Resistance Involve Loss of Insulin-Dependent Rac-Activation and Actin Remodeling in Muscle Cells

Abstract: In muscle cells, insulin elicits recruitment of the glucose transporter GLUT4 to the plasma membrane. This process engages sequential signaling from insulin receptor substrate (IRS)-1 to phosphatidylinositol (PI) 3-kinase and the serine/threonine kinase Akt. GLUT4 translocation also requires an Akt-independent but PI 3-kinase-and Racdependent remodeling of filamentous actin. Although IRS-1 phosphorylation is often reduced in insulin-resistant states in vivo, several conditions eliciting insulin resistance in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
220
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 182 publications
(234 citation statements)
references
References 52 publications
13
220
0
1
Order By: Relevance
“…Similar results were obtained in adipose tissue and 3T3-L1 adipocytes [164,165]. Additional evidences revealed that, in L6 myotubes, oxidative stress prevents insulin-induced actin reorganization [166]. Consequently, the molecular traffic required for insulin action could be regulated in a redox-dependent manner.…”
Section: Evidence For a Role Of Rons In Skeletal Muscle Insulin Resissupporting
confidence: 70%
“…Similar results were obtained in adipose tissue and 3T3-L1 adipocytes [164,165]. Additional evidences revealed that, in L6 myotubes, oxidative stress prevents insulin-induced actin reorganization [166]. Consequently, the molecular traffic required for insulin action could be regulated in a redox-dependent manner.…”
Section: Evidence For a Role Of Rons In Skeletal Muscle Insulin Resissupporting
confidence: 70%
“…More recent data extend this by showing PAK1 to be downstream of Rac1, and a Rac1 knock-out mouse exhibits defective insulin stimulated GLUT4 translocation (22). Because there is no evidence for the participation of Cdc42 in insulin action in skeletal muscle, it is very likely that Rac1 is the Rho family GTPase that signals to PAK1 in this tissue (20,22). Insulin was recently shown to reduce the amount of phosphocofilin in L6 rat skeletal myoblasts (19).…”
Section: Discussionmentioning
confidence: 93%
“…In those, when assessed in total cell lysates (i.e., when subcellular compartments are disregarded; these will be discussed in sect. IVC), intact IR and IRS proteins tyrosine phosphorylation were observed, as well as an intact insulin-stimulated interaction between IRS proteins and PI 3-kinase (211,357,429). In fact, these steps following insulin stimulation were even reported to be exaggerated in response to preexposure to oxidants, possibly reflecting the oxidant-induced inactivation of cellular phosphatases, particularly PTP1B (see sect.…”
Section: B Impaired Signal Transmission From Pi 3-kinase To Pkbmentioning
confidence: 99%